H-2B Guest Workers and the Critical Role They Play in US Forests. Issue 5 (27th April 2021) - Blinn, Charles R; O'Hara, Timothy J; Russell, Matthew B
Abstract: A survey of businesses that provide a variety of forest management services indicated the importance of H-2B guest workers in performing important tasks which facilitate management and sustainability of forest resources in the United States. Those workers accomplish a wide variety of tasks with tree planting being most common. Although the positions filled by those workers are first made available to US workers at government-mandated wage rates, few apply. Businesses reported that it is becoming increasingly difficult for them to secure all of their guest visas to fulfill their contacts. Although former President Donald J. Trump's proclamation on June 22, 2020, suspending entry of workers with H-2B visas, would have resulted in approximately one million acres not being reforested by respondents in 2020, a National Interest Exemption process provided a reprieve through the end of 2020. A long-term solution is needed to ensure that there are enough H-2B workers available to continue providing these important services.